2012
DOI: 10.1111/j.2042-3306.2012.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and selected pharmacodynamic effects of tramadol following intravenous administration to the horse

Abstract: This study confirms and extends previous studies describing the pharmacokinetics of tramadol following i.v. administration to the horse. Plasma tramadol concentrations exceeded those necessary for analgesia in human patients; however, further studies are necessary to determine plasma concentrations of tramadol necessary for analgesic efficacy in the horse. These results support further investigation of the analgesic efficacy of tramadol in the horse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
39
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 10 publications
11
39
3
3
Order By: Relevance
“…However, muscle tremors were present in all the treatments, similar to what was described by other authors who used μ opioid agonists (GIORGI et al, 2007;DHANJAL et al, 2009;KNYCH et al, 2013). It is believed that the decrease in the behavioral effects was due to the method of administration used in this study, the dilution of the drug and the increased time of infusion, proposed by SHILO et al (2007).…”
Section: In Horsessupporting
confidence: 60%
See 3 more Smart Citations
“…However, muscle tremors were present in all the treatments, similar to what was described by other authors who used μ opioid agonists (GIORGI et al, 2007;DHANJAL et al, 2009;KNYCH et al, 2013). It is believed that the decrease in the behavioral effects was due to the method of administration used in this study, the dilution of the drug and the increased time of infusion, proposed by SHILO et al (2007).…”
Section: In Horsessupporting
confidence: 60%
“…It is believed that the decrease in the behavioral effects was due to the method of administration used in this study, the dilution of the drug and the increased time of infusion, proposed by SHILO et al (2007). The adverse effects resolved by 20 minutes post tramadol administration, probably associated a rapid decline in plasma tramadol concentrations as reported by KNYCH et al (2013) for similarly doses evaluated in this study. It was concluded that the clinical alterations induced by the IV administration of tramadol in the doses of 1, 2 and 3mg kg -1 are light and transitory.…”
Section: In Horsessupporting
confidence: 55%
See 2 more Smart Citations
“…It is a centrally acting analgesic that has agonist activity at p opioid receptors and inhibits the reuptake of noradrenaline and serotonin. Although not licensed in horses, the pharmacokinetics and pharmacodynamics of intravenously, intramuscularly and orally administered tramadol have been investigated in this species (Giorgi and others 2007, Shilo and others 2008, Dhanjal and others 2009, Cox and others 2010, Stewart and others 2011, Knych and others 2013a, b). …”
Section: Tramadolmentioning
confidence: 99%